Comparison of Metaphorical Language Styles in the Novel Saman by Ayu Utami and the Novel Tabularasa by Ratih Kumala - Jusrin Efendi Pohan; Rosmita Ambarita (Modality Journal: International Journal of Linguistics and Literature, 2025)
Comparing the metaphorical language styles in these two novels is not merely about finding gaps in the author's mistakes, but rather more about the author's existence with his social reality. An author's paradigm will have implications for the surface structure of the story produced, compared to the visible deep structure. This is why comparative research is necessary on novels, so that it can be implemented in the order of values ​​and norms of social reality. The novel Saman by Ayu Utami and the novel Tabularasa by Ratih Kumala were conducted to reveal the author's skill in illustrating stories that are essentially different eras and are set against the background of each author's different social reality. This research was conducted naturally (positivism) rooted in qualitative to describe a phenomenon of the use of metaphorical language by the author. The method used by the researcher was content analysis by interpreting the contents of the two novels (Saman novel by Ayu Utami and Tabularasa novel by Ratih Kumala). The data collection technique was carried out using note-taking techniques, namely noting everything in the form of metaphorical language styles in the novel Saman by Ayu Utami and the novel Tabularasa by Ratih Kumala and comparing the metaphorical language styles of the two novels. After comparing, the researcher interpreted the meaning contained in the use of metaphorical language styles of the two novels. From the results of the interpretation, the results of the study showed that the comparison of the metaphorical language of the novel Saman by Ayu Utami and the novel Tabularasa by Ratih Kumala. The novel Tabularasa by Ratih Kumala reveals the influence of social reality and the author's background in creating the story. Evidently, the author of the novel Saman better reflects the personality of a woman who lived during the New Order to the reform era. The language style in this novel is able to cover up negative things in the minds of its readers. Although the author of the novel Tabularasa raises the issue of postmodern human life, the complexity of ideology, culture, race, and ethnicity for gender equality. However, this novel tells a complex and touching love story in the life journey of its main character.